Examining the Sociocultural Context of HIV‐related Risk Behaviors Among Kathoey (Male‐to‐female Transgender Women) Sex Workers in Bangkok, Thailand. (March 2016) - Nemoto, Tooru; Cruz, Taylor; Iwamoto, Mariko; Trocki, Karen; Perngparn, Usaneya; Areesantichai, Chitlada; Suzuki, Sachiko; Roberts, Colin
Abstract : N/A: Kathoey (male‐to‐female transgender) sex workers (KSW) in Thailand are at high risk for sexually transmitted infections; however, few qualitative studies have been conducted to understand the sociocultural context of engaging in HIV risk behaviors. A total of 24 participants were purposively sampled in Bangkok based on KSW work venues and substance use. Results revealed the importance of participants' understanding of the self in relation to establishing economic independence through sex work, which could then be used to re‐establish support from family, who often have not accepted a son's gender transition. Participants linked being kathoey to a belief in fate but did not view engagement in sex work in the same way. Different sex work venues exposed KSW to different risky situations. HIV prevention programs for kathoey must address the importance of economic security and its relation to social support and gender transition within a cultural‐ and work‐environment‐specific framework.